2022
DOI: 10.1038/s41467-022-29880-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends and associated factors for Covid-19 hospitalisation and fatality risk in 2.3 million adults in England

Abstract: The Covid-19 mortality rate varies between countries and over time but the extent to which this is explained by the underlying risk in those infected is unclear. Using data on all adults in England with a positive Covid-19 test between 1st October 2020 and 30th April 2021 linked to clinical records, we examined trends and risk factors for hospital admission and mortality. Of 2,311,282 people included in the study, 164,046 (7.1%) were admitted and 53,156 (2.3%) died within 28 days of a positive Covid-19 test. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 16 publications
1
29
2
Order By: Relevance
“…We reproduced the expected impact of age and comorbidities on COVID-19 severity. However, we did not find a significant effect of gender on COVID-19 severity, whereas other studies have found that the fatality rates are higher for men than in women (Beaney et al 2022), risk differences by gender have been shown to vary considerably with geography and time, suggesting that this interaction is mediated by social rather than biological factors (Danielsen et al 2022) and highlighting the benefits of studying epidemics in different populations That we found an increased risk of severe COVID-19 among certain non-citizen residents of Bahrain (`Other` category, Table 2), and within one of five governantes (Muharraq) indicates some degree of demographic heterogeneity of risk within the Bahraini population. Interestingly, the fact that South Asian patients had no detectable increased risk of severe disease, and that many South Asians in Bahrain are migrant workers, may mean that correlates of migrant worker status were not important determinants of COVID-19 outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…We reproduced the expected impact of age and comorbidities on COVID-19 severity. However, we did not find a significant effect of gender on COVID-19 severity, whereas other studies have found that the fatality rates are higher for men than in women (Beaney et al 2022), risk differences by gender have been shown to vary considerably with geography and time, suggesting that this interaction is mediated by social rather than biological factors (Danielsen et al 2022) and highlighting the benefits of studying epidemics in different populations That we found an increased risk of severe COVID-19 among certain non-citizen residents of Bahrain (`Other` category, Table 2), and within one of five governantes (Muharraq) indicates some degree of demographic heterogeneity of risk within the Bahraini population. Interestingly, the fact that South Asian patients had no detectable increased risk of severe disease, and that many South Asians in Bahrain are migrant workers, may mean that correlates of migrant worker status were not important determinants of COVID-19 outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…1 In children, SARS‐CoV‐2 infections are typically asymptomatic or associated with mild disease, and hospitalisation is uncommon. 2 , 3 Correspondingly, mortality is lower than in adults; the estimated infection fatality rate for people under 18 years of age in England during 2020–21 was five deaths per 100 000 infections 4 (adults: 2300 deaths per 100 000 infections 5 ).…”
mentioning
confidence: 99%
“…Unlike in adults, whom have a higher risk of developing aggressive forms of disease, and require more hospitalization days, most of the children in our study needed less than 5 days of hospital admission [12]. Furthermore, here occurs another reason for this short hospitalization of the included infants and children, 52.63% of mothers or caregivers decided that they want a discharge on request, contrary to the advice of the doctor.…”
Section: Discussionmentioning
confidence: 64%